RELATIONSHIP BETWEEN WORK DISCIPLINE, WORK ENVIRONMENT AND SUPERVISION OF EMPLOYEE PERFORMANCE AT WAROENG SPESIAL SAMBAL SURABAYA - Ambar Sari Yahya; I Gede Arimbawa; Elok Damayanti (Journal of World Conference (JWC), 2019)
This study aims to determine "relationship between work discipline, work environment and supervision of employee performance at Waroeng Spesial Sambal Surabaya ". This study used a quantitative research approach. The analytical method used the rank spearman correlation. The calculation process assisted by the program Statistical Package for the Social Sciences (SPSS) application, with number of 30 respondents by saturated sampling method (census). Based on the results of data management, work discipline with employee performance has a significant low relationship. Work environment and supervision with employee performance have a significant strong relationship. The results showed that the variables of work discipline, work environment and supervision were significantly related to employee performance. If there are other variables used to measure employee performance then the variable is not discussed in this study.